Plant functional types and microtopography mediate climate change responses of fine roots in forested boreal peatlands - Bucher, Melina; Ofiti, Nicholas O. E.; Malhotra, Avni (Frontiers in Forests and Global Change, 2023)
Peatlands store one-third of the world’s soil carbon, and their climate change response is a key unknown in the global carbon cycle-climate change feedback. In particular, peatland fine root responses to varied environmental changes are poorly constrained. Here, we synthesized fine root responses to warming and water level drawdown by performing a meta-analysis of existing data from boreal forested peatlands. We found seven studies and evaluated root responses from 65 observations. Overall, both warming (from 0 to 9.0°C) and water level drawdown (from 4.0 to 62.5 cm) increased fine root growth by over an order of magnitude, with plant functional type (PFT; graminoid, shrub, and tree) better predicting fine root biomass than treatment magnitude. We observed stronger responses for trees (+374.5% for warming and +868.6% for water level drawdown) than for shrubs (+44.0% for warming and +11.5% for water level drawdown) and graminoids (+59.5% for warming and −59.8% for water level drawdown). Among PFTs, tree fine roots increased significantly and non-linearly with increasing warming treatment, while graminoid fine roots responded significantly to lowering water level, decreasing 1.7% for every 1 cm decrease in water level. Fine roots in hollows, especially of shrubs, increased more strongly than those in hummocks, suggesting a possible flattening of peatland topography with sustained hollow growth from extended warming. Our synthesis highlights the important role of PFT’s in modulating fine root responses and the need for additional belowground data from these carbon-rich and globally relevant peatland soils. The altered fine root growth documented here, implies possible shifts in plant nutrient and water uptake as well as root inputs to soil carbon stocks, which in turn could strongly moderate and shape boreal peatland responses to future climate change.